(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the role and significance of marriage (nikah) and the walima ceremony in Islamic law and social life from a scholarly perspective. Marriage in Islam is analyzed as a sacred covenant that serves to establish the family, preserve lineage, and strengthen the moral foundations of society, based on verses from the Qur’an and authentic hadiths. The author emphasizes that marriage is not dependent on wealth or outward extravagance, but rather on the principles of blessing (barakah), responsibility, mutual respect, and lawful conduct. The article also reveals the true purpose of the walima ceremony, which is to publicly announce the marriage, strengthen kinship and brotherhood, and bring joy to the poor and those in need. The simple, modest, and waste-free wedding practices of the Prophet Muhammad (peace be upon him) are presented as an exemplary model for contemporary Muslim society. Furthermore, the article critically addresses the tendency toward extravagance in modern wedding practices and promotes an approach to marriage and walima that is consistent with Sharia, socially just, and morally grounded.